2017
DOI: 10.21831/jsd.v6i1.13403
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Perbedaan Intensitas Cahaya Dan Penyiraman Pada Pertumbuhan Jagung (Zea Mays L.) ‘Sweet Boy-02’

Abstract: AbstrakIntensitas cahaya dan ketersediaan air merupakan faktor-faktor yang menjadi penunjang maupun penghambat pertumbuhan tergantung kisaran yang mampu diterima tanaman. Tujuan penelitian ini adalah untuk mengetahui pengaruh intensitas cahaya dan penyiraman terhadap pertumbuhan tanaman jagung. Rancangan penelitian yang digunakan adalah Rancangan Acak Lengkap dengan 3 faktor intensitas cahaya (L1 : 63694 ; L2 : 11408 dan L3 : 3897 Lux) dan 3 faktor penyiraman (pemberian air sebanyak W1 : 2 L; W2 : 1,6 L; W3 : … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Light distribution is an important factor affecting maize photosynthesis [16]. The results of rescobch by [17], showed that light intensity had an effect on plant height, number of leaves, leaf width-length ratio, plant dry weight and root-tooth ratio of maize plants. Several maize varieties grown under the shade of oil palm aged 12 ycobs showed significant differences in plant height, amount of chlorophyll a and b, number of leaves, leaf length, leaf area, segment length, weight of cob without skin, dry cob weight, and seed weight.…”
Section: Table 2 Results Of Analysis Of Variance Of Treatment Effects and Interactions Between Treatments Onmentioning
confidence: 99%
“…Light distribution is an important factor affecting maize photosynthesis [16]. The results of rescobch by [17], showed that light intensity had an effect on plant height, number of leaves, leaf width-length ratio, plant dry weight and root-tooth ratio of maize plants. Several maize varieties grown under the shade of oil palm aged 12 ycobs showed significant differences in plant height, amount of chlorophyll a and b, number of leaves, leaf length, leaf area, segment length, weight of cob without skin, dry cob weight, and seed weight.…”
Section: Table 2 Results Of Analysis Of Variance Of Treatment Effects and Interactions Between Treatments Onmentioning
confidence: 99%
“…Wilson (1988) stated that increasing root temperature increased root activity in absorbing nutrients so that it could accelerate root formation. Akmalia and Suharyanto (2017) said that the lowest light intensity would allocate the biomass towards the canopy so that the value of the root-crown ratio is smaller.…”
Section: Root Canopy Ratiomentioning
confidence: 99%
“…Studi (M. N. I. Khan and Kabir, 2017) menunjukkan bahwa stress nanungan menyebabkna luas permukaan daun lebih besar dan daunnya lebih tipis dengan klorofil yang banyak namun pada Zea mays kondisi tercekam intensitas cahaya rendah disertai kekeringan menyebabkan kadar klorofil juga berkurang sehingga produktivitas menurun (Akmalia, Hafidha Asni;E. Suharyanto, 2017).…”
Section: Daununclassified
“…Pada akhirnya hal ini dapat menyebabkan perubahan penampakan daun dan mempengaruhi afinitasnya pada air. Sementara itu, naungan menyebabkan daun lebih tebal, indeks stomata menurun dan berkas pengangkut lebih berkembang pada Rhododenron agastum (Zhou et al, 2017) namun tidak pada Plectranthus amboinicus (Ekawati and Aziz, 2016) dan Zea mays (Akmalia and Suharyanto, 2017) yang menunjukkan bahwa daun lebih tipis dan berkas pengangkut kurang berkembang. Pada studi (Gupta et al, 2016), polusi di kota besar juga menyebabkan kerusakan sel penjaga, epidermis, dan mengubah bukaan stomata secara signifikan dan menurunkan ukuran juga densitas stomata (Lamalakshmi Devi et al, 2017).…”
Section: Daununclassified